Court as a means of dispute resolution in adoption cases in Malaysia: An appraisal of the Syariah Court’s decision on dispute relating to custody and maintenance of adopted children - Mohd, Azizah; A. Kadir, Nadhilah (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
Children generation are depending on adult as their guardian due to their vulnerability. They are the subject of custody and maintenance. Under Islamic law, parents are the most common guardian and are responsible for children’s custody and maintenance. Nevertheless, there are categories of children who are parentless or not living with their biological parents due to certain problems or situation like adoption. It follows that, as normal biological children, adopted children are also entitled to custody and maintenance in particular from their adoptive parents. The issues however arise whenever there is failure or neglect of care and maintenance of adopted children especially whenever the adopted children reached certain ages or in the event of divorce of the adoptive parents. This paper deals with court as a means to resolve dispute in matters relating to custody and maintenance of adopted children especially in Syariah Court in Malaysia. Examination will focus on Syariah Court’s decision when dealing with those issues. A comparison with other jurisdiction where relevant and necessary will also be done especially to provide a good findings for the paper